2017
DOI: 10.20524/aog.2017.0176
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Full Spectrum Endoscopy® (Fuse®, EndoChoice®) on adenoma detection: a prospective French pilot study

Abstract: BackgroundCurrently, colonoscopy and polypectomy are the gold standard methods for the prevention of incident cases of colorectal cancer. The use of a new colonoscope (Fuse®, EndoChoice®) with a larger view of up to 330° appears to improve the adenoma detection rate (ADR). We performed a prospective observational study concerning this scope. The primary endpoint was potentially omitted adenomas (POA), i.e. adenomas seen on the side screens that will not appear on the central display during colonoscopy withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The advent of a novel endoscopic platform, Full Spectrum Endoscopy ® (FUSE ® , EndoChoice Inc., Atlanta, Georgia, USA) that allows a panoramic field of view (245° for gastroscope, 330° for colonoscope), led to a revolution in the examination of GI regions that were previously considered as "invisible", such as the proximal side of colonic folds/flexures (6). It has been shown in literature that FUSE is superior to conventional colonoscopy, as it is associated to a reduction in overall and proximal colorectal adenoma miss rates (7,8). Similarly, the new upper GI endoscope represents a sophisticated technical innovation, as it allows an accurate inspection of both gastric and duodenal mucosa (including the peri-ampullary region) in a single procedure (9).…”
Section: Discussionmentioning
confidence: 99%
“…The advent of a novel endoscopic platform, Full Spectrum Endoscopy ® (FUSE ® , EndoChoice Inc., Atlanta, Georgia, USA) that allows a panoramic field of view (245° for gastroscope, 330° for colonoscope), led to a revolution in the examination of GI regions that were previously considered as "invisible", such as the proximal side of colonic folds/flexures (6). It has been shown in literature that FUSE is superior to conventional colonoscopy, as it is associated to a reduction in overall and proximal colorectal adenoma miss rates (7,8). Similarly, the new upper GI endoscope represents a sophisticated technical innovation, as it allows an accurate inspection of both gastric and duodenal mucosa (including the peri-ampullary region) in a single procedure (9).…”
Section: Discussionmentioning
confidence: 99%
“…In order to compensate the 'key-hole' effect during an endoscopic examination of the GI tract, as e.g. the colon, multiple-view endoscopes such as 'third eye' endoscopes [9,10] or 'fullspectrum endoscopy' (FUSE)" [11,12] for these systems have improved, the acquired image data can still not be used for an image-based documentation of the endoscopic examination and the clinical report of type and location of a finding. Using the urinary bladder as an example of a hollow organ to be assessed and examined with an endoscope, it has recently been shown, that it is possible to provide a so-called 'endoscopic panorama' or 'endoscopic map' of the bladder directly during the endoscopic examination in real time [13,14], which can afterwards be used for an image-based documentation of the bladder-examination, see Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…7 The estimated potentially omitted adenomas without the side-viewing cameras of FUSE has been shown to be 29% for men and 19% for women. 8 FUSE has also been shown to outperform conventional colonoscopy with right-colon scope retroflexion in the detection of missed adenomas, both overall and in the proximal colon, even when performed by experienced endoscopists. 9 Our group previously reported that FUSE increased overall center-wide ADR by 5.4% when compared with TFV in a real world community based setting.…”
mentioning
confidence: 98%
“…The views provided by these imagers importantly include the proximal aspect of haustral folds, where more than 70% of missed lesions may be located 7. The estimated potentially omitted adenomas without the side-viewing cameras of FUSE has been shown to be 29% for men and 19% for women 8. FUSE has also been shown to outperform conventional colonoscopy with right-colon scope retroflexion in the detection of missed adenomas, both overall and in the proximal colon, even when performed by experienced endoscopists 9.…”
mentioning
confidence: 99%